A low-carbon permeable brick based on waste asphalt powder and its preparation method

By adding shell powder to asphalt waste powder and performing high-temperature reconstruction, combined with microbial carbon sequestration technology, low-carbon permeable bricks are prepared, which solves the problem of asphalt waste powder pollution and achieves efficient utilization of materials and low-carbon production.

CN116177952BActive Publication Date: 2025-03-04FUYANG NORMAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211647826.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-03-04
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize asphalt waste powder, which causes it to pollute the environment and occupy land resources.

Method used

By adding shell powder to the asphalt waste powder, performing component adjustment and high-temperature reconstruction, a new gelling material is prepared, and a low-carbon permeable brick is made using microbial carbon sequestration technology.

Benefits of technology

It realizes the effective utilization of asphalt waste powder, reduces waste powder pollution, improves the carbon sequestration efficiency of the materials, and meets the requirements of low-carbon production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177952B_ABST
    Figure CN116177952B_ABST
Patent Text Reader

Abstract

The present invention provides a low-carbon permeable brick based on waste asphalt powder and a preparation method thereof, and relates to the technical field of building blocks. The specific steps of the preparation method are: S1, adding shell powder to waste asphalt powder, preparing a new type of cementitious material by means of component adjustment and high-temperature reconstruction, as the raw material of S2; S2, based on microbial carbon fixation technology, determining the ratio of each raw material by volume method, and mixing and stirring each raw material; S3, molding and curing the mixture obtained in S2 to obtain a low-carbon permeable brick. After the waste asphalt powder is treated by means of component adjustment and high-temperature reconstruction, it has a certain gelling ability and can be used as a related building material, effectively reducing waste powder pollution, and adding microbial powder that can secrete carbonic anhydrase to improve carbon fixation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building blocks and relates to a low-carbon permeable brick based on asphalt waste powder and its preparation method. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] With the acceleration of urbanization, urban surfaces are being covered by various buildings and concrete pavements, significantly increasing the proportion of impermeable surfaces. In response, relevant departments have proposed the construction of "sponge cities," enabling cities to have good "resilience" in adapting to environmental changes and responding to natural disasters caused by rainwater. Permeable pavements are an important component of "sponge cities," and their construction requires a large amount of permeable bricks and other building materials.

[0004] Asphalt waste powder, also known as recycled waste powder from asphalt mixing plants, is a large amount of micron-sized dust generated during the mixing process of asphalt mixtures. Direct emission of this dust would cause serious air pollution, so modern asphalt mixing plants are equipped with dust removal devices to collect it. Due to the rapid development of road infrastructure construction, the consumption of asphalt mixtures is substantial. An asphalt mixing plant generates 8-10 tons of waste powder for every 100 tons of asphalt concrete produced, amounting to tens of millions of tons annually nationwide. Currently, there are no good methods for disposing of this waste powder, and most of it is disposed of through landfill. This not only occupies land resources but also pollutes the environment. If this waste powder could be effectively utilized, it could both turn waste into treasure and solve the environmental pollution problem.

[0005] The proportions of each component in waste asphalt powder are shown in Table 1 below.

[0006] Table 1

[0007]

[0008] Asphalt waste powder originates from dust generated during asphalt mixing. It consists of small particles, typically less than 0.075 mm in diameter, with a large specific surface area, eliminating the need for grinding. Furthermore, due to the incorporation of a large amount of soil during its generation, its chemical composition differs from that of the mixing raw materials. Asphalt waste powder has low activity; when directly used to prepare permeable bricks, its mechanical strength fails to meet specifications. Summary of the Invention

[0009] To address the aforementioned technical problems, this invention provides a low-carbon permeable brick based on asphalt waste powder and its preparation method. The invention develops a novel cementitious material by adjusting the composition of asphalt waste powder and reconstructing it at high temperature. Simultaneously, carbon-fixing microorganisms are added to produce low-carbon permeable bricks, which not only realizes waste utilization but also benefits environmental protection.

[0010] To achieve the above objectives, the technical solution of the present invention is as follows:

[0011] The first aspect concerns the preparation method of low-carbon permeable bricks based on asphalt waste powder, specifically including the following steps:

[0012] S1. Add shell powder to asphalt waste powder and prepare a new type of cementitious material through component adjustment and high-temperature reconstruction, which serves as the raw material for S2.

[0013] S2. Based on microbial carbon fixation technology, the proportion of each raw material is determined by volumetric method, and the raw materials are mixed and stirred.

[0014] S3. The mixture obtained in S2 is molded and cured to obtain low-carbon permeable bricks.

[0015] In S1, the component adjustment process is as follows:

[0016] Using the theoretical limit of lime content, based on the oxide content in asphalt waste powder and shell powder, and according to the conservation of CaO, the mass of asphalt waste powder and shell powder required for C2S production is calculated, and the mass ratio of asphalt waste powder to shell powder is determined.

[0017] In cement production, the theoretical amount of lime required for every 1.0% reaction of acidic oxides is as follows: (For ease of calculation, C4AF is rewritten as "C3A" and "CF").

[0018] The amount of CaO required to form C3S from 1.0% SiO2 is 3 × CaO molecular weight / SiO2 molecular weight = 3 × 56.08 / 60.09 = 2.8 (CaO molecular weight is taken as 56.08, SiO2 molecular weight is taken as 60.09, the same below);

[0019] The amount of CaO required to form C2S from 1.0% SiO2 is: 2 × CaO molecular weight / SiO2 molecular weight = 2 × 56.08 / 60.09 = 1.87;

[0020] The amount of CaO required to form C3A from 1.0% Al2O3 is: 3 × CaO molecular weight / Al2O3 molecular weight = 3 × 56.08 / 101.96 = 1.65 (Al2O3 molecular weight is taken as 101.96);

[0021] The amount of CaO required to form "CF" from 1.0% Fe2O3 = CaO molecular weight / Fe2O3 molecular weight =

[0022] 56.08 / 159.70 = 0.35 (The molecular weight of Fe2O3 is taken as 159.70).

[0023] Furthermore, let the mass of asphalt waste powder be x, and the mass of shell powder be y.

[0024]

[0025] Wherein, Si1: SiO2 content in asphalt waste powder; Si2: SiO2 content in shell powder; A1: Al2O3 content in asphalt waste powder; A2: Al2O3 content in shell powder; F1: Fe2O3 content in asphalt waste powder; F2: Fe2O3 content in shell powder; C1: CaO content in asphalt waste powder; C2: CaO content in shell powder;

[0026] The required amount of shell powder (y) can be determined based on the mass of asphalt waste powder (x).

[0027] The high-temperature reconstruction process is as follows:

[0028] Asphalt waste powder and shell powder are mixed and stirred until uniform, then calcined at high temperature and kept at that temperature for a period of time before cooling to allow the powder to react completely and produce a cementitious material. The cementitious material produced is mainly composed of C2S and also contains a certain amount of C3S.

[0029] Furthermore, after the heating temperature reaches 1350℃, it is kept at that temperature for 1 hour, and then cooled.

[0030] Furthermore, the CO2 generated during the high-temperature reconstruction process is collected, cooled, and added in step S2.

[0031] In S2, the specific steps are as follows:

[0032] Add coarse aggregate and acetic acid solution to a concrete mixer and mix for 30 seconds to make the surface of coarse aggregate uniformly wet. Add the cementitious material prepared in S1 and the additives. Introduce CO2 generated during high-temperature reconstruction and mix for 30 seconds to form a cementitious material slurry shell to coat the coarse aggregate. Add the remaining acetic acid solution during the mixing process and mix for about 180 seconds.

[0033] The coarse aggregate is selected from basalt stones with a particle size of 2.36 mm to 4.75 mm and an apparent density of 2976 kg / m³. 3 ;

[0034] The acetic acid solution can accelerate the dissolution of calcium in the cementitious material, release a large amount of low-activity calcium in the asphalt waste powder that exists in solid solution, and provide an internal calcium source for the entire system.

[0035] The additive is a microbial powder capable of secreting carbonic anhydrase, selected from Bacillus mucilaginosus. Preferably, the activity of the Bacillus mucilaginosus powder is 5.0 × 10⁻⁶. 9 The optimal culture environment is between pH 7.5 and 8, with a cell / g concentration. Preferably, the apparent density of the Bacillus mucilaginosus powder used is 1200 kg / m³. 3 It enhances the carbon fixation efficiency of cementitious materials through its catalytic effect and can maintain its activity during the subsequent use of permeable bricks, thus continuously exerting the carbon fixation effect and showing obvious environmental advantages.

[0036] Furthermore, carbon dioxide gas collected and cooled during the high-temperature reconstruction process is introduced to induce carbonation in the minerals, and the carbon fixation efficiency of the cementitious material is improved through the catalytic action of microorganisms that secrete carbonic anhydrase.

[0037] Furthermore, the proportions of various raw materials are determined using the volumetric method. The formula for the volumetric method is as follows:

[0038]

[0039] Among them, M G The amount of coarse aggregate used per cubic meter, kg / m³ 3 ;ρ G The apparent density of coarse aggregate is kg / m³. 3 kg / m 3 M W The amount of water used is expressed in kg / m³. 3 ;ρ W M is the apparent density of water. S The amount of cementitious material used per cubic meter, kg / m 3 ;ρ S The apparent density of the cementitious material is kg / m³. 3 M Z The dosage of additive per cubic meter, kg / m³ 3 ;ρ Z The apparent density of the additive is kg / m³. 3 P represents the target porosity; the water is an acetic acid solution with a concentration of 1.00 mol / L.

[0040] In S3, the specific steps are as follows: using the static pressure molding method, lubricating oil is evenly applied to the surface of the test mold as required by the standard. The mixture is poured into the test mold, and a compressive stress of 20MPa is applied to the mixture using a load. The pressure is maintained for 1 minute to form the mixture. After standing for about 8 hours to stabilize the shape, the mold is removed, and the prepared specimen is placed in a curing chamber with a relative humidity of 60% and a temperature of 25℃ for 18 hours to obtain the finished low-carbon permeable brick.

[0041] Secondly, a low-carbon permeable brick prepared using the above steps can be used for road paving.

[0042] The beneficial effects of this invention are as follows:

[0043] 1. This invention provides a reasonable ratio of asphalt waste powder and high-calcium content materials, and treats the asphalt waste powder by adjusting the components and high-temperature reconstruction to give it a certain cementing ability, so that it can be used as a related building material, effectively reducing waste powder pollution and providing a new treatment path for waste powder.

[0044] 3. This invention utilizes a high-temperature reconstruction process to calcine the mixed powder, so that the fully calcined mixed powder has a certain amount of C2S, thereby improving the activity of asphalt waste powder.

[0045] 4. In this invention, carbon dioxide generated during the high-temperature reconstruction process is introduced into the brick-making process to provide raw materials for the mineral carbonation reaction, thereby reducing carbon dioxide emissions and achieving low-carbon production.

[0046] 5. In the carbonation reaction of the cementitious material, the present invention adds an additive (microbial powder) that can secrete carbon anhydrase to improve carbon fixation efficiency. Attached Figure Description

[0047] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0048] Figure 1 The present invention provides a flowchart of a method for preparing low-carbon permeable bricks based on the activation of asphalt waste powder. Detailed Implementation

[0049] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0050] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0051] Example 1

[0052] A method for preparing low-carbon permeable bricks based on the activation of asphalt waste powder, the process is as follows: Figure 1 As shown, it includes the following steps:

[0053] S1. Add shell powder to asphalt waste powder and prepare a new type of cementitious material through component adjustment and high-temperature reconstruction, which serves as the raw material for S2.

[0054] S2. Based on microbial carbon fixation technology, the proportion of each raw material is determined by volumetric method, and the raw materials are mixed and stirred.

[0055] S3. The mixture obtained in S2 is molded and cured to obtain low-carbon permeable bricks.

[0056] In S1, the asphalt waste powder is obtained from an asphalt mixing plant. The particle size of the waste powder is mostly less than 0.075 mm, and the apparent density is 2580 kg / m³. 3 The main components of asphalt waste powder are SiO2, Fe2O3, Al2O3, CaO, and MgO, with proportions of 24.83%, 2.11%, 4.77%, 35.70%, and 0.97%, respectively. Shell powder is a powder made from ground seashells commonly found in the market; its 95% component is calcium carbonate, and its apparent density is 1080 kg / m³. 3 ;

[0057] Shell powder was added to adjust the composition of the asphalt waste powder. The mass ratio of asphalt waste powder to shell powder was calculated according to the following formula (the calcium carbonate in the shells is converted to CaO, so the CaO content in the shell powder is 53%):

[0058]

[0059] Wherein, x represents the mass of asphalt waste powder, and y represents the mass of shell powder; Si1: SiO2 content in asphalt waste powder; Si2: SiO2 content in shell powder; A1: Al2O3 content in asphalt waste powder; A2: Al2O3 content in shell powder; F1: Fe2O3 content in asphalt waste powder; F2: Fe2O3 content in shell powder; C1: CaO content in asphalt waste powder; C2: CaO content in shell powder;

[0060] The calculated ratio of waste asphalt powder to shell powder is 4:1;

[0061] According to the calculated proportions, the uniformly mixed powder with adjusted components is added to the calcining tank, calcined and kept at a temperature of 1350℃ for 1 hour. The reconstructed cementitious material in the calcining tank is then sent to a cooling storage chamber for cooling.

[0062] In S2, the specific steps are as follows:

[0063] Add coarse aggregate and acetic acid solution to a concrete mixer and mix for 30 seconds to make the surface of coarse aggregate uniformly wet. Add the cementitious material prepared in S1 and the additives. Introduce CO2 generated during high-temperature reconstruction and mix for 30 seconds to form a cementitious material slurry shell to coat the coarse aggregate. Add the remaining acetic acid solution during the mixing process and mix for about 180 seconds.

[0064] The mix design of permeable paving bricks is performed using the volumetric method, and the formula is as follows:

[0065]

[0066] Among them, M G The amount of coarse aggregate used per cubic meter, kg / m³ 3 ;ρ G The apparent density of the coarse aggregate is taken as 2976 kg / m³ in this embodiment. 3 M W The amount of water used is expressed in kg / m³. 3 ;ρ W M is the apparent density of water. S The amount of cementitious material used per cubic meter, kg / m 3 ;ρ S The apparent density of the cementitious material is taken as 1830 kg / m³ in this embodiment. 3 M Z The dosage of additive per cubic meter, kg / m³ 3 ;ρ Z The apparent density of the additive is 1200 kg / m³ in this embodiment. 3 P is the target porosity; the water is a 1 mol / L acetic acid solution; then ρ W Take 1050 kg / m 3 (The density of an acetic acid solution with a concentration of 1 mol / L);

[0067] Preferably, in this embodiment, the target porosity of the permeable brick is 15%, the water-cement ratio is 0.3, the additive dosage is 1% of the mass of the cementitious material, and the coarse aggregate is selected from basalt stones with a particle size of 2.36mm to 4.75mm. The water-cement ratio refers to the ratio of water used per cubic meter of concrete to the total amount of cementitious material, which affects the strength and fluidity of the cementitious paste. In this embodiment, to ensure the strength of the cementitious paste and to allow the fluidity of the cementitious material to fully coat the coarse aggregate, the water-cement ratio is set to 0.3, i.e., M... W M S =0.3;

[0068] The appropriate material usage per cubic meter of low-carbon permeable bricks was calculated, with coarse aggregate usage at 1753.22 kg / m³. 3Cementitious material usage: 237.66 kg / m³ 3 Additive dosage: 4.22 kg / m 3 Acetic acid solution dosage: 127.82 kg / m³ 3 ;

[0069] The additive is a microbial powder that can secrete carbonic anhydrase, selected from Bacillus mucilaginosus, which improves the carbon fixation efficiency of the cementitious material through its catalytic action.

[0070] In step S3, the well-stirred mixture is poured into a test mold and formed using a static pressing method.

[0071] In this embodiment, a static pressure molding method is adopted. Lubricating oil is evenly applied to the surface of the test mold as required by the standard. The mixture is poured into the test mold, and a compressive stress of 20MPa is applied to the mixture by load. The pressure is maintained for 1 minute to form the mixture. After standing for about 8 hours to stabilize the shape, the mold is removed, and the prepared specimen is sent to a curing box with a relative humidity of 60% and a temperature of 25°C for 18 hours to obtain the finished low-carbon permeable brick.

[0072] Example 2

[0073] The low-carbon permeable bricks prepared in Example 1 were subjected to compressive strength, flexural strength and splitting tensile strength tests in accordance with the "Standard for Concrete Pavement Bricks" (GB28635-2012) and the "Standard for Permeable Pavement Bricks and Permeable Pavement Panels" (GBT25993-2010).

[0074] The measured strengths were 21.57 MPa, 5.31 MPa and 3.56 MPa, respectively, which meet the relevant requirements in the "Standard for Permeable Pavement Bricks and Permeable Pavement Panels" and can be applied to the paving of permeable pavement bricks.

[0075] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder, characterized in that: The steps include: S1, adding shell powder to asphalt waste powder, preparing cementitious material by adjusting components and reconstructing at high temperature as raw material of S2; S2. Based on microbial carbon fixation technology, the ratio of each raw material is determined by volume method, and each raw material is mixed and stirred; S3, molding and curing the mixture obtained in S2 to obtain low-carbon permeable bricks; The raw materials in S2 include: cementitious material, coarse aggregate, acetic acid solution, and additives; The additive includes microbial powder capable of secreting carbonic anhydrase; In S1, the high-temperature reconstruction step is: adding the uniformly mixed powder after component adjustment into the calcining tank, calcining and keeping warm, the calcining temperature is 1350°C, and keeping warm for 1 hour, and sending the reconstructed gelling material in the calcining tank to the cooling storage bin for cooling.

2. The method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder according to claim 1, characterized in that: In S1, waste asphalt powder is obtained from an asphalt mixing plant.

3. The method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder according to claim 1, characterized in that: In S1, the mass ratio of waste asphalt powder to shell powder is calculated according to the following formula: Among them, the mass of asphalt waste powder is x, and the mass of shell powder is y; : SiO2 content in asphalt waste powder; : SiO2 content in shell powder; : Al2O3 content in asphalt waste powder; : Al2O3 content in shell powder; : Fe2O3 content in asphalt waste powder; : Fe2O3 content in shell powder; : CaO content in asphalt waste powder; : CaO content in shell powder.

4. The method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder according to claim 1, characterized in that: In S1, the CO2 generated during the high-temperature reconstruction process is collected, cooled, and added to S2.

5. The method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder according to claim 1, characterized in that: In S2, the mix design of permeable pavement bricks is carried out by volume method, and the calculation formula is as follows: in, The amount of coarse aggregate per cubic meter, kg / m 3 ; is the apparent density of coarse aggregate, kg / m 3 ; The amount of water per cubic meter, kg / m 3 ; is the apparent density of water, kg / m 3 ; The amount of cementitious material per cubic meter, kg / m 3 ; is the apparent density of the cementitious material, kg / m 3 ; The dosage of additive per cubic meter, kg / m 3 ; is the apparent density of the additive, kg / m 3 ; P is the target porosity; the water is an acetic acid solution with a concentration of 1.00 mol / L; The target porosity is 15%, : =0.3; the additive dosage is 1% of the mass of the cementitious material; the coarse aggregate is selected from basalt stones with a particle size of 2.36mm~4.75mm.

6. The method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder according to claim 1, characterized in that: In S2, the additive is a microbial powder capable of secreting carbonic anhydrase, selected from Bacillus colloids, and the activity of Bacillus colloids powder is 5.0×10 9 cell / g.

7. The method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder according to claim 1, characterized in that: The mixing and stirring method in S2 is: According to the mix ratio, weighed coarse aggregate and 20% acetic acid solution are added into a concrete mixer and stirred once for 30 seconds to make the surface of the coarse aggregate evenly wet. Then, cementitious materials and additives are added and CO2 generated during high-temperature reconstruction is introduced to form a cementitious material slurry shell to wrap the surface of the coarse aggregate. The remaining acetic acid solution is added while stirring and stirred for a second time. The second stirring time is 180 seconds.

8. The method for preparing low-carbon permeable bricks based on the activation of waste asphalt powder according to claim 1, characterized in that: In S3, the specific steps are: adopt the static pressure molding method, evenly apply lubricating oil on the surface of the test mold required by the specification standard, pour the mixture into the test mold, use the load to apply a compressive stress of 20MPa to the mixture, and stabilize the pressure for 1 minute to shape the mixture, let it stand for 8 hours to stabilize the shape, remove the mold, and send the prepared test piece to a curing box with a relative humidity of 60% and a temperature of 25°C for curing for 18 hours to obtain a finished low-carbon permeable brick.

9. A low-carbon permeable brick prepared by the method for preparing a low-carbon permeable brick based on the activation of waste asphalt powder as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for making microorganism-slag carbon-fixed water permeable brick

    CN110183194A

  • Environment-friendly greening brick containing recycled waste powder of asphalt mixing station and preparation method of greening brick

    CN112592136A